2017
DOI: 10.1111/1759-7714.12475
|View full text |Cite
|
Sign up to set email alerts
|

Epac1, PDE4, and PKC protein expression and their association with AKAP95, Cx43, and cyclinD2/E1 in breast cancer tissues

Abstract: BackgroundThis study was conducted to investigate the exchange protein directly activated by cAMP (Epac1), PDE4, and PKC expression in breast cancer tissues, and the correlation between these proteins and AKAP95, Cx43, cyclin D2, and cyclin E1.Methods PV‐9000 two‐step immunohistochemistry was used to analyze protein expression.ResultsThe positive rate of Epac1 protein expression in breast cancer tissues (58%) was higher than in para‐carcinoma tissues (10%) (P < 0.05). There were no significant differences in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…In addition, pharmacological inhibition of EPAC1 by ESI-09 suppresses cell proliferation and migration, while inducing cell cycle arrest and apoptosis in breast cancer cells (567). Increased expression of EPAC1 in 58% of breast cancer patients (29/ 50) was reported, as compared with a 10% positive rate (1/10) in controls (446). These studies demonstrate fresh and exciting potentials for novel therapeutic strategies targeting EPAC1 in breast and gastric/esophagus cancer treatments.…”
Section: B Role Of Epac In Cancersmentioning
confidence: 73%
“…In addition, pharmacological inhibition of EPAC1 by ESI-09 suppresses cell proliferation and migration, while inducing cell cycle arrest and apoptosis in breast cancer cells (567). Increased expression of EPAC1 in 58% of breast cancer patients (29/ 50) was reported, as compared with a 10% positive rate (1/10) in controls (446). These studies demonstrate fresh and exciting potentials for novel therapeutic strategies targeting EPAC1 in breast and gastric/esophagus cancer treatments.…”
Section: B Role Of Epac In Cancersmentioning
confidence: 73%
“…Existing immune histochemical results of our laboratory [19][20][21] showed that the expression of AKAP95, cyclin D1, cyclin D2 and cyclin E1 in cancer tissues was higher than that in adjacent tissues, and expression of above proteins was correlated. CCNDs and CCNEs are considered as proto-oncogenes, and cyclin Ds and cyclin Es are mainly synthesized and play a role in G1 phase [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…However, several research reported that EPAC1 depict a protective role in glioblastoma [ 62 , 63 , 64 ], bladder cancer [ 65 ] and renal cancer [ 66 ]. What’s more, EPAC1 can either promote or attenuate cancer progression in breast cancer [ 67 , 68 , 69 ], leukaemia [ 70 , 71 ], neuroendocrine cancer [ 72 ], ovarian cancer [ 73 , 74 , 75 , 76 ] and prostate cancer [ 77 , 78 , 79 , 80 ]. The reason for dual functions of EPAC1 in the same cancer is very complicated and can be influenced by cancer cell types as well as genomic and transcriptomic differences, but the integrated mechanism remains elusive.…”
Section: Neuropeptide and Epac Signalling Pathways In Cancermentioning
confidence: 99%
“…The expression level of EPAC1 is associated with breast cancer patient prognosis [ 68 ]. The protein level of EPAC1 in breast cancer tissues was significantly upregulated versus para-carcinoma tissues.…”
Section: Neuropeptide and Epac Signalling Pathways In Cancermentioning
confidence: 99%